2016
DOI: 10.17269/cjph.107.5471
|View full text |Cite
|
Sign up to set email alerts
|

Are inequalities produced through the differential access to play opportunities at school? A call to level the playing field

Abstract: Children's play is characterized as pleasurable, but it is also viewed as critical for child health and well-being. Yet over the past decade, play researchers and advocates from various disciplines have suggested that there are decreasing opportunities for children to play, particularly at school. One concern is that the changing play environment in schools is reducing children's active play options and is thereby contributing to increases in childhood obesity. Building on findings from the QUébec Adipose and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…The ways in which time spent outdoors in children has been studied to date varies widely in terms of participant age, methodology, and foci, confounding scholars’ ability to compare findings. Many studies also conflate outdoor play and physical activity, as well as children’s IM with active travel, which undermines the value of travel and outdoor play that is not active [ 30 , 103 , 104 ]. A majority of studies on these topics to date have also been carried out primarily in urban areas in the US, Canada, and Australia, and do not consider the potentially differing outdoor play patterns of children living in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…The ways in which time spent outdoors in children has been studied to date varies widely in terms of participant age, methodology, and foci, confounding scholars’ ability to compare findings. Many studies also conflate outdoor play and physical activity, as well as children’s IM with active travel, which undermines the value of travel and outdoor play that is not active [ 30 , 103 , 104 ]. A majority of studies on these topics to date have also been carried out primarily in urban areas in the US, Canada, and Australia, and do not consider the potentially differing outdoor play patterns of children living in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Although organized PAs may be easier to implement, encourage and study, they have been shown to explain very little in the variation of children’s MVPA [ 52 ]. In addition, it has been suggested that an emphasis on encouraging children to engage in supervised or adult-led, structured physical activities rather than encouraging free, unsupervised, or unstructured play to meet the MVPA guidelines may be contributing, in part, to the decline in fitness among Canadian children [ 53 ] and a decrease in PA among children more generally [ 54 , 55 ]. In addition, these results suggest some promising implications for cost-effective interventions for schools wishing to increase PA levels among their students.…”
Section: Discussionmentioning
confidence: 99%
“…According to Active Healthy Kids Canada (2012), active play is fun, freely chosen, self-directed, and spontaneous. 1 This form of play can be distinguished by its vigor and generally involves greater energy expenditure than play but less energy expenditure than exercise. 2 Active play has recently caught the attention of public health scholars as a promising strategy for promoting children’s well-being.…”
Section: Purposementioning
confidence: 99%
“…7 However, increased demands of formal schooling, parental concerns over child safety from injuries, and the decreased availability of play spaces in children’s environments are also believed to have contributed to play disappearing from children’s lives. 1,8…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation